Risk management in agriculture through information and communication technologies in selected states of Malaysia - Ali, Muhammad (2018)
Agricultural risk management is getting priority by the farmers to overcome problems prevailing due to climatic variations and affecting farms and farmers’ behavioral intention to use ICTs for managing agriculture related risks. As ICTs have proved cheap, speedy, easy to operate in sharing, learning various practices for managing risks at individual and collective level, so, existing condition of ICT usage alongwith risk management techniques were deemed necessary to examine at various parts of the country. Agriculture extension services in this context were also required to determine at the field level. Therefore, the prime focus of this study was to examine management of risk in agriculture through Information and Communication Technologies at selected states in Malaysia. The emprical research was conducted: 1) to identify the ICT technologies, sources of information use, agriculture extension services, existing networks and adaptation by the respondents in managing agriculture risk; 2) to examine attitude level, subjective norm level, perceived behavioral control level and intention level to use ICTs for agricultural risk management; 3) to evaluate the relationship between socio-demographic factors and intention to use ICTs for managing agricultural risks by the respondents; 4) to assess relationship between attitude, subjective norm, perceived behavioral control and intention to use ICTs for agricultural risk management; and 5) to determine the influence of attitude, subjective norms, perceived behavioral control (IVs) on the intention (DV) of farmers to use ICTs for risk management in agriculture. The data were collected through suvery method in which pre designed questionnaire was used as research instrument. Multistage cluster sampling technique was used to gather data from total 360 farmers. The data were randomly collected from three states which were reflecting East zone (Pahang and Terengganu), South zone (Johor) and North zone (Kedah). The statistical analysis techniques administered in this study were descriptive analysis, chi square, Pearson correlation and multiple regression. The results showed that mobile was used by majority of farmers. Additionally, the results of chi square revealed that education, dependent size, land ownership and income had significant association (p<0.05) with intention of farmers. The result of bivariate correlation matrix revealed that there was statistically significant plus positive relationship between attitude (r =0.705), subjective norms (r = 0.551), perceived behavioral control (r = 0.642) and intention at 0.01 level with p=0.0001. The results of regression analysis depicted that there is high relationship (R= 0.730) between IVs and intention to use ICTs for agricultural risk management. Moreover, about 53% (adj. R2) variance in intention to use ICTs is explained by IVs. In conclusion, farmers’ intention to use ICTs for agricultural risk management was influenced by attitude, social pressure and personal control. Additionally, extension services providers need to pay more attention towards farmers to integrate digital technologies in order to get equipped in advance for any kind of disasters. The study recommends that capacity building programmes should be initiated to use ICTs for agricultural risk management for the extension field staff and farmers.